Risk of biliary diseases in patients with type 2 diabetes or obesity treated with tirzepatide: A meta‐analysis - Jie Gong; Fengwei Gao; Kangyi Jiang; Qingyun Xie; Xin Zhao; Zehua Lei (Journal of Diabetes Investigation)
ABSTRACT Objective To investigate the risk of biliary diseases in patients with type 2 diabetes mellitus (T2DM) or obesity treated with tirzepatide. Methods Literature searches were performed using the PubMed, Web of Science, Cochrane Library, and CNKI databases until 20 May 2024. Randomized controlled studies (RCTs) investigating the safety of tirzepatide vs placebo/other hypoglycemic drugs in patients with T2DM or obesity were included. The safety outcomes mainly included the incidence of cholelithiasis, pancreatitis, cholecystitis, and gallbladder/biliary diseases. Cochrane Collaboration's tool for assessing the risk of bias was used to assess the quality of literature. Heterogeneity was evaluated using I2 statistics. Results A total of 12 high‐quality RCTs (involving 12,351 patients) were included. The results of meta‐analysis showed that tirzepatide was associated with gallbladder/biliary diseases (RR = 1.52; 95%CI: 1.17–1.98; I2 = 0%, P = 0.76) and cholelithiasis (RR = 1.67; 95%CI: 1.14–2.44; I2 = 0%, P = 0.95). Subgroup analysis based on the dose of tirzepatide found no dose–response relationship between different doses of tirzepatide and the risk of gallbladder/biliary diseases and cholelithiasis. Conclusions Based on the data currently available, tirzepatide is associated with the development of cholelithiasis in patients. However, the findings from RCTs still need to be further investigated in many post‐marketing safety surveillance programs.